Kemiskinan Perkotaan dan Angka Partisipasi Pendidikan Tinggi di Indonesia - Utami, Yuli; Djunarto; Sahetapy, Willyan (Jurnal EMT KITA, 2024)
This research aims to investigate the relationship between urban poverty and higher education participation in Indonesia using time series data during the 1998-2021 period. The analytical model used is simple linear regression which is then estimated using the ordinary least squares (OLS) approach. Through empirical data analysis, this research finds that urban poverty has a significant negative influence on higher education participation, indicating that high levels of poverty in urban environments can be a barrier to higher education access and participation for economically marginalized communities.